A Novel Role for Triglyceride Metabolism in Foxp3 Expression - Howie, Duncan; Ten Bokum, Annemieke; Cobbold, Stephen Paul; Yu, Zhanru; Kessler, Benedikt M.; Waldmann, Herman (Frontiers in Immunology, 2019)
Lipid metabolism plays a key role in many cellular processes. We show here that regulatory T cells have enhanced lipid storage within subcellular lipid droplets (LD). They also express elevated amounts of both isoforms of diacylglycerol acyl transferase (DGAT1 & 2), enzymes required for the terminal step of triacylglycerol synthesis. In regulatory T-cells (Tregs), the conversion of diacylglycerols to triacylglycerols serves two additional purposes other than lipid storage. First, we demonstrate that it protects T cells from the toxic effects of saturated long chain fatty acids. Second, we show that Triglyceride formation is essential for limiting activation of protein kinase C via free diacyl glycerol moieties. Inhibition of DGAT1 resulted in elevated active PKC and nuclear NFKB, as well as impaired Foxp3 induction in response to TGF. Thus, Tregs utilise a positive feedback mechanism to promote sustained expression of Foxp3 associated with control of LD formation.